IMAGE CONTRAST ENCHANCEMENT USING BRIGHTNESS PRESERVATION DYNAMIC HISTOGRAM EQUALIZATION - K. Radhika, Eedala Siva Poojitha, Bathini Charitha Venkata Sai, Kolapalli Vyshnavi Sai, Kothaluru Sivani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In the digital image processing domain, image enhancement plays an important role for various applications like astronomy, satellite image processing, geographical imaging, and consumer electronics etc. This work gives the implementation of brightness preserved histogram specification-controlled histogram equalization techniques for enhancing the image quality by preserving the brightness and by enhancing contrast of image by the usage of dynamic stretching. The proposed method provides the better quantitative and qualitative approach compared to the various other schemes; algorithms proposed by various researchers in this field of image enhancement.